Local carbachol application induces oral microvascular recruitment and improves gastric tissue oxygenation during hemorrhagic shock in dogs - Hof, Stefan; Lingens, Lara; Michels, Marius; Marcus, Carsten; Kuebart, Anne; Herminghaus, Anna; Bauer, Inge; Picker, Olaf; Truse, Richard; Vollmer, Christian (Frontiers in Immunology, 2024)
Introduction: Hemorrhagic shock is characterized by derangements of the gastrointestinal microcirculation. Topical therapy with nitroglycerine or iloprost improves gastric tissue oxygenation but not regional perfusion, probably due to precapillary adrenergic innervation. Therefore, this study was designed to investigate the local effect of the parasympathomimetic carbachol alone and in combination with either nitroglycerine or iloprost on gastric and oral microcirculation during hemorrhagic shock.Methods: In a cross-over design five female foxhounds were repeatedly randomized into six experimental groups. Carbachol, or carbachol in combination with either nitroglycerine or iloprost were applied topically to the oral and gastric mucosa. Saline, nitroglycerine, or iloprost application alone served as control groups. Then, a fixed-volume hemorrhage was induced by arterial blood withdrawal followed by blood retransfusion after 1h of shock. Gastric and oral microcirculation was determined using reflectance spectrophotometry and laser Doppler flowmetry. Oral microcirculation was visualized with videomicroscopy. Statistics: 2-way-ANOVA for repeated measurements and Bonferroni post-hoc analysis (mean ± SEM; p < 0.05).Results: The induction of hemorrhage led to a decrease of gastric and oral tissue oxygenation, that was ameliorated by local carbachol and nitroglycerine application at the gastric mucosa. The sole use of local iloprost did not improve gastric tissue oxygenation but could be supplemented by local carbachol treatment. Adding carbachol to nitroglycerine did not further increase gastric tissue oxygenation. Gastric microvascular blood flow remained unchanged in all experimental groups. Oral microvascular blood flow, microvascular flow index and total vessel density decreased during shock. Local carbachol supply improved oral vessel density during shock and oral microvascular flow index in the late course of hemorrhage.The specific effect of shifting the autonomous balance by local carbachol treatment on microcirculatory variables varies between parts of the gastrointestinal tract. Contrary to our expectations, the improvement of gastric tissue oxygenation by local carbachol or nitroglycerine application was not related to increased microvascular perfusion. When carbachol is used in combination with local vasodilators, the additional effect on gastric tissue oxygenation depends on the specific drug combination. Therefore, modulation of tissue oxygen consumption, mitochondrial function or alterations in regional blood flow distribution should be investigated.